The Use of Euphemism in Karonese Language Langkat - Surbakti, Agustina Br; Tresiany, Yeni Winda (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This research was conducted to identify the function of euphemism used in Karonese Laguage Langkat. This research applied qualitative descriptive approach. The qualitative data were taken from interview in karonese people at villange bahorok, langkat. The instrument for collecting the data through interview. The result of the analysis from interview the data taken from the respondents show that euphemism used in Karonese language divided in some categories such pronoun, adjective, verb, and noun. The use of Euphemism in Karonese language is not only for the words, but also in some phrases. In express the euphemism, karonese culture used Euphemism to communication. And the last one is karonese people usually use Euphemism to express the euphemism in situation or condition. The content of social values in the mourning tradition of karonese’s culture has function to motivate, advice, amuse, and strengthen the condolences family. And in educational function that can be as the reflection for the people about the importance of this tradition for readers especially young generation.